Phlorotannins from brown algae: a review on their antioxidant mechanisms and applications in oxidative stress-mediated diseases - Phang, Shou Jin; Teh, Huey Xhin; Looi, Mee Lee; Arumugam, Bavani; Fauzi, Mh Busra; Kuppusamy, Umah Rani (Journal of applied phycology, 2023)
Phlorotannins are polyphenolic compounds that are exclusively derived from marine brown algae. The molecular structure of phlorotannins with numerous phenol rings endows them with excellent radical scavenging and antioxidant properties. Oxidative stress plays a central role in the pathogenesis of many diseases, including neurodegenerative diseases, hepatic diseases, skin diseases, diabetes and retinal diseases. Therefore, phlorotannins have been explored as potential antioxidant compounds to counteract the oxidative damage induced during disease development. The antioxidant mechanisms of phlorotannins are not only limited to the direct scavenging of reactive oxygen species (ROS) but also via the inhibition of ROS production and the activation of antioxidant defence mechanisms. In this review, we highlight the antioxidant properties and mechanisms of action of phlorotannins in the context of several oxidative stress-mediated diseases using evidence from in vitro and in vivo studies. Despite the promising antioxidant potential of phlorotannins, their translational applications are hindered by the poor bioavailability and biostability. Hence, the encapsulation of phlorotannins into various drug carriers like nanoparticles and nanofibres has been greatly explored. Taken together, these findings propose phlorotannins as potential therapeutics in the advancement of current treatment available for different oxidative stress-mediated diseases.